BPM-based framework for e-government processes improvement: legal requirements integration. (2017) - Cherouana, Amina; Mahdaoui, Latifa; Khadraoui, Abdelaziz
An e-government system is articulated around a set of governmental processes offering a new era of greater convenience in stakeholder access to governmental information and services. However, a survey of e-government implementations has brought out that most governmental institutions have not transformed and improved their supporting processes. This has led to a big gap between the deployed portals and the expected promises because they attribute more attention to their web-based portals away from their supporting governmental processes. Consequently, this work considers the Government Process Management lifecycle, especially the designing phase in order to design efficient governmental processes according to their legal basis. Indeed, for governmental processes, all design choices should be backed by legal-texts. To do so, the developed approach is articulated around two main levels, namely the legal design and the operational design. Its main purpose is to produce common governmental processes models, explicit legal requirements representation, and shared domain concepts and services.